Penerapan Teori Keadilan Terhadap Pembagian Harta Bersama Pasca Perceraian - Safira Maharani Putri Utami; Siti Nurul Intan Sari Dalimunthe (Jurnal USM Law Review)
This research aims to examine the application of the division of marital assets after divorce by analyzing the case in decision number 2802/Pdt.G/2018/Dpk. The focus of this research is on the division of marital assets and how the theory of justice is applied in the division process. This research is important as it highlights the division of marital assets as a sensitive issue in society, and the importance of justice as a key factor in the division that can influence court decisions. Therefore, it is necessary to analyze the factors considered by the panel of judges in cases involving the division of marital assets. This research adopts a normative legal research method by analyzing the applicable legal regulations and supported by other legal materials, including primary, secondary, and tertiary legal sources. The findings of this research indicate that the existing regulations governing the division of marital assets do not fully meet the criteria of justice for wives who bear a double burden in marriage. Judges are allowed to deviate from existing laws and engage in contra legem practices to achieve justice for all parties involved in the marriage.